ANALISIS PERBEDAAN KINERJA SAHAM PADA PERUSAHAAN YANG MELAKUKA CORPORATE SOCIAL RESPONSIBILITY DAN PERUSAHAAN YANG TIDAK MELAKUKAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Winarso, Beni Suhendra; Kurniawati, Indah (Universitas Ahmad Dahlan, 2019)
The purpose of this study was to examine differences in the performance of stock in a company that does Corporate Social Responsibility and the company does not undertake Corporate Social Responsibility in companies listed on the Indonesia Stock Exchange. Â Samples of this company is a manufacturing company that does Corporate Social Responsibility and the company does not undertake Corporate Social Responsibility in 2013. The stock performance is analyzed by using the ratios earnings price ratio, price-to-book ratio and earnings per share and do independent samples test or Mann Whitney test for testing the significance of differences.Â Â The results of this study indicate that outlines the company's stock performance that does Corporate Social Responsibility has no difference with the stock performance of companies that do not do a Corporate Social Responsibility. This is shown by the results obtained in the analysis of financial ratios which includes price earnings ratio, price to book value and earnings per share.